Análise da diversidade e selecção em macieira 'Bravo' - Martins, Antero (2009)
An experimental population containing 149 genotypes of the ‘Bravo’ apple randomly sampled all over it growing regions, as submitted to mass genotypic selection through the methods previously developed or other species such as grapevine. This study led to determining the coefficient of genotypic variation of some characteristics, as a quantifier of intra-varietal genetic diversity. The global values reveal the existence of a considerable diversity, but the comparative analysis is, at presente, affected by the lack of reference values for other ancient varieties. On the other hand, the values per sub regions are in general higher in “Beira Interior”, but the differences are moderate, which can suggest a frequent exchange of materials among the three regions and the consequent homogenization of the diversity. As a result of this work, it was also possible to select nineteen superior genotypes, with a predicted genetic gain of 25 % in the yield, which can be used immediately for new plantations. With these clones three field trials were also installed, at “Viseu”, “Moimenta da Beira” and “Covilhã”, in order to make clonal selection.